2019
DOI: 10.3389/fnins.2019.01203
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Integration of Brain Images for MRI-Based Diagnosis in Schizophrenia

Abstract: Magnetic resonance imaging (MRI) has been proposed as a source of information for automatic prediction of individual diagnosis in schizophrenia. Optimal integration of data from different MRI modalities is an active area of research aimed at increasing diagnostic accuracy. Based on a sample of 96 patients with schizophrenia and a matched sample of 115 healthy controls that had undergone a single multimodal MRI session, we generated individual brain maps of gray matter vbm, 1back, and 2back levels of activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…The machine learning (ML) technique is a new approach that can extract relevant information from images and construct models to determine the probability of disease onset, and it can make a higher accurate prediction compared with conventional methods [ 5 , 6 , 13 , 17 , 18 ]. Salvador et al [ 15 ] achieved 75.76% accuracy in schizophrenia diagnosis, and de Filippis et al [ 5 ] reported that support vector machine associated with other ML techniques could achieve accuracy close to 100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The machine learning (ML) technique is a new approach that can extract relevant information from images and construct models to determine the probability of disease onset, and it can make a higher accurate prediction compared with conventional methods [ 5 , 6 , 13 , 17 , 18 ]. Salvador et al [ 15 ] achieved 75.76% accuracy in schizophrenia diagnosis, and de Filippis et al [ 5 ] reported that support vector machine associated with other ML techniques could achieve accuracy close to 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI (fMRI) and structural MRI (sMRI) are gaining importance and becoming more widely acceptable techniques with the potential to help diagnose neurological illnesses [8][9][10][11], including schizophrenia [5,12,13]. An increasing number of studies have reported that multimodal brain data can improve diagnostic accuracy by combining the information obtained from different MRI imaging modalities [8,[14][15][16]. The machine learning (ML) technique is a new approach that can extract relevant information from images and construct models to determine the probability of disease onset, and it can make a higher accurate prediction compared with conventional methods [5,6,13,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there has been some work which incorporates multimodal measures to differentiate mental disorders via deep learning. Salvador et al [20] used gray matter volumes, functional activation † Yuhui Du, corresponding author Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. Copyrights for components of this work owned by others than ACM must be honored.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal features provide information from different perspectives allowing models to understand the neural substrates associated with schizophrenia with complementary information from various modalities. Previous studies illustrated the benefits of combining sMRI and dMRI as well as fMRI for the classification of schizophrenia using handcrafted featurebased machine learning (Isobe et al, 2016;Lei et al, 2020;Saarinen et al, 2020;Salvador et al, 2019), suggesting possible future research with incorporation of additional neuroimaging modalities.…”
Section: Multimodal Inputs and Complex Topologies Improved Classification Accuracymentioning
confidence: 99%
“…Studies using transfer learning approaches that utilize powerful pre-trained 2D CNN networks to extract features from deep layers are also lacking. Of note, multimodal feature extraction from different neuroimaging modalities is critical for understanding the neural substrates underlying schizophrenia from complementary perspectives, potentially leading to higher classification performance (Lei et al, 2020;Lerman-Sinkoff et al, 2019;Salvador et al, 2019). The automatic feature learning capability of CNN enables more prominent integration of multimodal inputs, yet, multi-channel 2D and 3D CNN have not been employed and evaluated for schizophrenia discrimination.…”
Section: Introductionmentioning
confidence: 99%